1996
DOI: 10.1002/(sici)1096-9861(19960701)370:3<405::aid-cne10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of serotonin receptor subtypes 5-HT2A, 5-HT2C, and 5-HT6 with neuropeptides in rat striatum

Abstract: There are two primary output pathways from the striatum: a projection to the globus pallidus, and projection to the substantia nigra. Certain striatally expressed neuropeptides are differentially distributed between these two pathways. Specifically, enkephalin is expressed in striatopallidal neurons, whereas substance P and dynorphin are expressed in striatonigral neurons. Several serotonin receptors are also prominently expressed in the striatum, but little is known about how they fit into the molecular neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
2
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(95 citation statements)
references
References 42 publications
(49 reference statements)
10
82
2
1
Order By: Relevance
“…Previous studies have reported the expression of almost all 5-HT receptor subtypes in the striatum (Blandina et al, 1989;Jakeman et al, 1994;Waeber et al, 1994;Bruinvels et al, 1994;Patel et al, 1995;Gerald et al, 1995;Ward and Dorsa, 1996). However, the 5-HT receptors expressed by striatal cholinergic interneurons are unknown.…”
Section: Striatal Cholinergic Interneurons Express 5-ht2c 5-ht6 Andmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported the expression of almost all 5-HT receptor subtypes in the striatum (Blandina et al, 1989;Jakeman et al, 1994;Waeber et al, 1994;Bruinvels et al, 1994;Patel et al, 1995;Gerald et al, 1995;Ward and Dorsa, 1996). However, the 5-HT receptors expressed by striatal cholinergic interneurons are unknown.…”
Section: Striatal Cholinergic Interneurons Express 5-ht2c 5-ht6 Andmentioning
confidence: 99%
“…Another 5-HT receptor expressed at significant levels in the striatum is the 5-HT6 receptor (Ruat et al, 1993;Ward and Dorsa, 1996;Gerard et al, 1997). The involvement of these receptors was assessed by using the selective antagonist SB 258585.…”
Section: -Ht Receptor Classes Involved In the Serotonergic Excitatormentioning
confidence: 99%
See 3 more Smart Citations